Occurrence, removal, and ecological risk assessment of Emerging organic contaminants in an industrial WWTP - Yunhai Zhang; Ruiqin Yin; Xueping Yu; Jiawei Zhou; Yong Chen; Yongjun Zhang (Water Resources and Industry, 2025)
Emerging organic contaminants (EOCs) pose significant impacts to the aquatic environment due to their persistence and toxicity. This study analyzed the occurrence of 68 EOCs in eight categories in the water phase and sludge at an industrial WWTP in China consisting of a conventional biotreatment and an advanced treatment (fiber filtration plus chlorination). The results demonstrated effective removal of pharmaceuticals (PhMs) and antibiotics (ATBs) through biotreatment (84.8 % for PhMs, 79.2 % for ATBs) and advanced treatment (78.6 % for PhMs, 64.7 % for ATBs). The total removal efficiencies of Pesticides (PEST), phthalate esters (PAEs), organophosphate esters (OPEs), and UV filters (UVFS) were 56.4 %, 22.3 %, 56.7 %, and 49.6 %, respectively. In contrast, no removal of perfluoroalkyl chemicals (PFAS) (−68.5 %). Mass balance analysis revealed that OPEs, PhMs and UVFS were mainly removed through biodegradation, while ATBs were mainly removed through sludge adsorption. The study also found a correlation between the partition coefficients (LogKd) and their octanol-water partition coefficients (logKow). The ecological risk quotient highlighted perfluorooctanesulfonate (PFOS), imidacloprid (IMI), and clothianidin (CLO) as high-risk contaminants. This study reveals the combined process of secondary and advanced treatment in WWTPs can effectively remove EOCs, such as PhMs (96.7 %) and ATBs (92.6 %), providing guidance for the development of targeted technologies to mitigate the risks of EOCs.